Chronic Psychosis in a Patient with Usher Syndrome - Abhay Keshava Bhat; Sheetal Reshram Meshram; Maithili S. Umate; Prakhar D. Jain (Annals of Indian Psychiatry)
Usher syndrome refers to a group of inherited disorders characterized by visual and auditory impairment. The risk of psychosis in Usher syndrome is higher than that in the general population and is difficult to approach and treat in light of sensory impairment. We present a case of a male with continuous psychotic symptoms for 20 years, in the setting of undiagnosed progressively deteriorating visual and auditory function, with details of treatment given. Possible underlying mechanisms of psychosis in such cases are discussed in brief.